Digital Entertainment to Support Toddlers’ Language and Cognitive Development - Endar Rachmawaty Linuwih; Nopita Trihastutie (TEKNOSASTIK, 2020)
This current research aimed at seeing how English nursery rhymes and kids’ songs as learning media support toddlers who are not living in an English speaking country (Indonesia) but exposed to the English language media during their normal baby-sitting times to learning English. To observe how two Indonesian toddlers learned English language in their early critical period of language acquisition through co-watching activity, Early Development Instrument which focuses on language and cognitive development domain with reading awareness and reciting memory subdomain was applied to observe two subjects after 15 month treatments (from age 10-24 months). The results show that the media and the co-watching activity are able to support the toddlers’ understanding of the English words spoken and their ability to produce the intelligent pronunciation of those words. The interesting fact reveals that English which is normatively learned merely as a foreign language to most Indonesian people is no longer something far-off to the toddlers who are exposed to it through English nursery rhymes and kids’ songs online since they are at the very young age. They naturally tend to be bilingual since at the same time they learn their mother tongue.